Wild trees bear fruit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In Mwanza district, Malawi, thirteen villages have, for the last five years, been involved in a project to make fruit juice from indigenous species - Baobab and Tamarind. As a result people in the area are now planting more indigenous trees, rather than cutting them for charcoal and firewood.